Risk factors associated with Acute Respiratory Infection (ARI) among children under 10-years in Rohingya refugee camp - Oishi, Shafiqua Nawrin; Alam, Nazmul (Recent Research in Science and Technology, 2020)
Acute respiratory infections are cause by bacterial, fungal or viral infections of the respiratory tract. Very young and older aged people are most vulnerable of these infections lead to difficulties from fever, cough, nasal discharge, sputum production, fatigue, wheezing, pain on swallowing, at times ear infections and meningitis. With huge number of Rohingya influx in Bangladesh, camps are overly crowded allowing many infectious diseases to transmit easily. Although there are researches that have been conducted in this area, there remains a huge gap of research in these camps where children being vulnerable are mostly suffering from respiratory disease such as Acute Respiratory Infection (ARI). This cross-sectional study investigated the risk factors associated with ARI among children less than 10 years in Rohingya refugee camps. After collecting information based on their demographic, anthropometric, history of respiratory problem, accommodation and nutritional status, it was found that about 21.6% of 259 children under this study had symptoms of ARI. Living in congested housing and with lack of nutritious food children were found negatively associated with ARI.